2016
DOI: 10.1007/s12291-016-0599-0
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Xanthine Oxidase, Ischemia Modified Albumin, Nitric Oxide with Antioxidants in Non Pregnants, Pre and Post-delivery of Normal Pregnants and Preeclampsia

Abstract: Preeclampsia is a multisystem disorder involves altered homeostasis of oxidants-antioxidants, inflammatory process and endothelial dysfunction. The present study aim was to determine the levels of oxidative stress parameters (malondialdehyde, protein carbonyl, ischemia modified albumin and xanthine oxidase), nutrient antioxidants (vitamin C and vitamin E), enzyme antioxidants (catalase, superoxide dismutase, glutathione peroxidase glutathione reductase), total antioxidant status (TAS) and its association with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 29 publications
1
15
0
1
Order By: Relevance
“…Increased IMA during the first trimester has been shown in pregnant with premature preeclampsia and then proposed as an early indicator of this complication [146]. This indicator returns to normal within 48 hours of birth, with symptoms of preeclampsia disappearing [147]. A meta-analysis of publications available in NCBI PubMed and other databases conducted by Reddy et al [153] showed that IMA is a potentially useful biomarker for PE with reasonable accuracy (AUC = 0:860).…”
Section: Obstetrics and Gynecologymentioning
confidence: 99%
“…Increased IMA during the first trimester has been shown in pregnant with premature preeclampsia and then proposed as an early indicator of this complication [146]. This indicator returns to normal within 48 hours of birth, with symptoms of preeclampsia disappearing [147]. A meta-analysis of publications available in NCBI PubMed and other databases conducted by Reddy et al [153] showed that IMA is a potentially useful biomarker for PE with reasonable accuracy (AUC = 0:860).…”
Section: Obstetrics and Gynecologymentioning
confidence: 99%
“…Similarly, Bambrana et al, (4) reported reversal of the changes in oxidants-antioxidants homeostasis evinced within 48 h after delivery in PE.…”
Section: Discussion:-mentioning
confidence: 81%
“…Thereafter, Bambrana et al (4) reported that in PE women XOA, MDA and UA levels were significantly increased, while total antioxidant status (TAS) and levels of SOD and glutathione reductase (GR) were decreased in PE versus normotensive pregnant women. Recently, Barneo-Caragol et al (28) found serum UA levels were significantly different between non-pregnant and normotensive pregnant women in the 1 st , 2 nd and 3 rd trimesters and increases gradually as the pregnancy progresses.…”
Section: Discussion:-mentioning
confidence: 99%
See 1 more Smart Citation
“…In our earlier research reports, we presented increased concentration of oxidative stress and decreased total antioxidant status [12] and also increased xanthine oxidase activity with the inverse relation of nitric oxide in pre-eclampsia [13,14]. There is seldom information available with respect to phospholipase A 2 and plasma elastase in pre-eclampsia.…”
Section: Introductionmentioning
confidence: 98%